For Ruminators, the Emotional Future Is Bound to the Emotional Past: Heightened Ruminative Disposition Is Characterized by Increased Emotional Extrapolation. (July 2015) - Watkins, Edward; Grafton, Ben; Weinstein, Stacey Megan; MacLeod, Colin
Processing mode theory proposes that rumination is characterized by abstract processing that involves increased thinking about the implications of emotional events, which derives the prediction that heightened ruminative disposition will be associated with elevated emotional extrapolation from current events when formulating future expectancies. To test this, we used a novel Emotional Extrapolation Assessment Task that measured individual differences in the degree to which the emotional tone of initial events influences relative expectancy for subsequent events that are emotionally consistent or inconsistent with this initial event. In Experiment 1, ruminative disposition was associated with increased self-reported expectancy for negative subsequent events relative to positive subsequent events. As predicted, in Experiment 2, heightened ruminative disposition was associated with increased emotional extrapolation, assessed using a comprehension latency performance-based measure.